Citizens' preferences for development outcomes and governance implications - Falk, Thomas; Vorlaufer, Tobias; Brown, Lawrence; Domptail, Stephanie; Dallimer, Martin (Wiley, 2021)
People's preferences influence national priorities for economic development and ecological integrity. Often policymakers and development agents base their actions on unclear assumptions about such preferences. This paper explores rural citizens' preferences for economic and ecological development outcomes and how they differ within and between communities. We collected data from three purposely selected communities representing dominant social‐ecological systems in the transboundary Cubango‐Okavango River basin in southern Africa. We used contingent ranking survey experiments, which are a novel methodological advance in policy related research. This included a qualitative experimental design process that provided a broad framing underpinning the research. The contingent ranking itself allowed us to simultaneously assess: (i) respondents' priorities for development domains; and (ii) respondents' preferences for the ordering of outcomes in diverse domains. We found relatively strong preference homogeneity within and between communities. Economic development was given high priority across all communities. At the same time, all communities expressed a high preference for a healthy river system providing stable water quality and quantity. This does not mean that our respondents prioritised nature conservation. They showed low preferences for preserving biodiversity and forests that provide fewer local benefits. This is of high governance relevance. The results point at development domains where policymakers can most likely expect stronger buy‐in from citizens. Understanding citizens' preferences help to better align national development priorities with what citizens want.